Crossbow injuries: A case report with experimental reconstruction study and a systematic review of literature. (April 2021) - Maiese, A.; Santoro, P.; La Russa, R.; De Matteis, A.; Turillazzi, E.; Frati, P.; Fineschi, V.
Abstract: In modern times crossbow - a ranged weapon diffused during Middle Ages - is increasing its popularity in recreational hunting and sports; crossbow bolts have a great penetration capacity, despite their low initial velocity. Great concerns emerge when considering that notwithstanding crossbow is a potentially lethal distance weapon, it is easy to obtain without having to undertake any tests on the buyer's mental or physical health. Although rare, crossbow injuries can be challenging for the forensic pathologist due to great similarities with other wounds pattern (gunshots wounds or injury due to sharp force). Especially when the arrow is removed from its original position or the body is decomposed, identification of the weapon can be difficult. According to forensic literature, suicides, homicides and non-lethal injuries by crossbow have been reported up to the present day. We followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) indications in the identification and selection of studies and reviewed a series of cases of both fatal and non-fatal crossbow injuries, according to the manner of death (homicide, suicide, accidental). The casuistic part of this paper deals with an attempted murder of a 21-year old man: a case of non-lethal crossbow injury of the thorax in which an interdisciplinary approach, involving forensic inspection, ballistic and radiology tests, led to solve the case. Highlights: Crossbow is a potentially lethal distance weapon, easy to obtain and to operate that not requiring practice so. Crossbows have a great penetration capacity in soft tissues and bones, causing a wide range of lesions. We described a case of attempted homicide, but literature reports cases homicide, accidental injuries and suicides. A CT scan should always be performed both in dead and survived victims because can be of great help..